2011
DOI: 10.1007/s00268-011-1352-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Integrated Robotic Approach for Suprapancreatic D2 Nodal Dissection for Treating Gastric Cancer: Technique and Initial Experience

Abstract: Our novel robotic approach for D2 nodal dissection in gastric cancer is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 36 publications
(40 reference statements)
2
104
0
5
Order By: Relevance
“…However, it is difficult to perform lymph node dissection during LG for those used to performing open gastrectomy (Huang et al, 2012). Previous studies reported that robot-assisted lymph node dissection was feasibility of a precision and bloodless (Uyama et al, 2012). In all, our data revealed that robotic assisted lymph nodes harvested was safe and could achieve an adequate lymph nodes harvested comparable to LG.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, it is difficult to perform lymph node dissection during LG for those used to performing open gastrectomy (Huang et al, 2012). Previous studies reported that robot-assisted lymph node dissection was feasibility of a precision and bloodless (Uyama et al, 2012). In all, our data revealed that robotic assisted lymph nodes harvested was safe and could achieve an adequate lymph nodes harvested comparable to LG.…”
Section: Discussionsupporting
confidence: 53%
“…Robotic gastrectomy (RG) is able to dissect lymph node precisely and offers some benefits over conventional laparoscopic surgery. Studies on robotic gastrectomy have been widely reported (Song et al, 2009;Hur et al, 2010;Lee et al, 2011;Park et al, 2012;Uyama et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In 1994, Kitano et al 27. reported the first laparoscopic Billroth I gastrectomy and since then, gastrectomy is increasingly being carried out laparoscopically and in some cases, robotically in Japan 28. Most importantly, the results of two ongoing randomized control trials comparing laparoscopic and open gastrectomy for gastric cancer are awaited 29.…”
Section: Gastric Surgerymentioning
confidence: 99%
“…Thus, from the initial experience, robotic surgery can be carried out safely if it is conducted by a surgeon experienced in laparoscopic surgery. The learning curve of robotic gastrectomy demonstrates a quicker adaptation with most studies reporting 11‐25 cases to be sufficient for experienced gastric cancer surgeons,20, 35, 36 whereas 40‐60 cases of surgical experience are required to overcome the learning curves associated with laparoscopic gastrectomy 37, 38. However, there is no study directly comparing the learning curve effect of robotic surgery in cases of surgeons having no laparoscopic experience.…”
Section: Perioperative Outcomesmentioning
confidence: 99%